Rural Finance and Food Security Study in Bangladesh, 1994 - International Food Policy Research Institute (International Food Policy Research Institute, 2010)
The Rural Finance and Food Security survey was conducted in Bangladesh in 1994 to analyze the determinants of the formation and participation in group-based rural financial institutions and the effects of participation on household resource allocation, income generation, and food and nonfood consumption. The community level survey covered 120 villages, and the household survey covered 1,181 individuals in 350 households in 7 villages in 5 thanas. The study included credit groups formed by three Nongovernmental organizations (NGOs)- Association for Social Advancement (ASA), Bangladesh Rural Advancement Committee (BRAC), and Rangpur-Dinajpur Rural Services (RDRS). Selection of respondents for the household surveys was based on stratified random sampling, with household possession of land as the stratifier, irrespective of membership in NGO programs. Household surveys focused on collecting data related to household composition, occupation, education, school participation, dwelling characteristics, assets, expenditures, food consumption, anthropometric measurements of women and children, and use of the Food for Education (FFE) system.